PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR SEGIEMPAT BERBASIS METODE PENEMUAN TERBIMBING (GUIDED DISCOVERY) UNTUK PESERTA DIDIK KELAS VII SMP/MTs - Muh. Qardawi Hamzah; Andi Halimah; Baharuddin Abbas (Faculty of Tarbiyah and Teacher Training, 2019)
The objective of this research is to develop a mathematics learning tool for rectangular flat structure material based on valid, practical, and effective guided discovery methods. The type of this research used is Research & Development by referring to the 4D model, namely: define, design, develop, and disseminate. The product developed is in the form of lesson plans, student textbooks and LKPD which are based on guided discovery methods on rectangular flat material. The instruments used in this study were validation sheets, observation sheets of learning device implementation, learning management observation sheets, student activity observation sheets, student and teacher response questionnaire sheets and learning achievement test. Based on the results of the trials conducted, it was found that (1) the results of the validation of learning tools namely RPP and LKPD were in the valid category, while the student textbook was in the valid category; (2) practically, based on observations of the implementation of learning devices in the overall implementation category, the teacher’s response to student textbooks is 100% and LKPD gives a response of 90%; while the analysis of students’ response data to student textbooks there were 99.5% of students who gave positive responses, and 82,5% of students who gave positive responses to LKPD. Effectively based on the management of learning obtained are in the very good category, student activity in the excellent category, and tests learning outcomes are in the high category with an average test score of 12 from an ideal score of 15. It can be concluded that at the trial stage the development of the quadrilateral flat mathematics learning tool based on the guided discovery method of grade VII SMP/MTs met the valid, practical, and effective criteria. AbstrakPenelitian ini bertujuan untuk mengembangkan perangkat pembelajaran matematika materi bangun datar segiempat berbasis metode penemuan terbimbing yang valid, praktis, dan efektif. Jenis penelitian yang digunakan adalah Research & Development (Penelitian dan Pengembangan) dengan mengacu pada model 4D yaitu: define, design, develop, dan disseminate. Produk yang dikembangkan berupa RPP, buku ajar siswa dan LKPD yang berbasis metode penemuan terbimbing pada materi bangun datar segiempat. Instrumen yang digunakan dalam penelitian ini adalah lembar validasi, lembar pengamatan keterlaksanaan perangkat pembelajaran, lembar pengamatan pengelolaan pembelajaran, lembar pengamatan aktivitas peserta didik, lembar angket respons peserta didik dan guru serta tes hasil belajar. Berdasarkan hasil uji coba yang dilakukan, diperoleh bahwa (1) Hasil validasi perangkat pembelajaran yaitu RPP dan LKPD berada pada kategori valid dan buku ajar siswa berada pada kategori valid, (2) Praktis berdasarkan hasil pengamatan keterlaksanaan perangkat pembelajaran berada pada kategori terlaksana seluruhnya, respons guru terhadap buku ajar siswa adalah 100% dan LKPD memberikan respons 90%; sedangkan analisis data respons peserta didik terhadap buku ajar siswa terdapat 99,5% siswa yang memberi respons positif, dan 82,5% siswa yang memberi respons positif pada LKPD, (3) Efektif berdasarkan pengelolaan pembelajaran diperoleh berada pada kategori sangat baik, aktivitas peserta didik dalam kategori sangat baik, dan tes hasil belajar berada dalam kategori tinggi dengan skor rata-rata tes adalah 12 dari skor ideal 15. Disimpulkan bahwa pada tahap uji coba yang dilaksanakan pengembangan perangkat pembelajaran matematika materi bangun datar segiempat berbasis metode penemuan terbimbing kelas VII SMP/MTs telah memenuhi kriteria valid, praktis dan efektif.